Reprocessable and degradable bio-based polyurethane by molecular design engineering with extraordinary mechanical properties for recycling carbon fiber. (14th October 2022) - Sun, Yinglu; Tian, Xinxin; Xie, Haopu; Shi, Biru; Zhong, Jiahui; Liu, Xiangdong; Yang, Yuming
Abstract: In recent years, bio-based covalent adaptable networks (CANs) and vitrimers have developed rapidly in order to meet the renewable and sustainable requirements. It should be emphasized that the performance of the network need be upgraded and optimized to substitute petroleum-based polymers. Herein, a series of high-performance bio-based polyurethane were synthesized containing castor oil, isosorbide, vanillin derivative and 4, 4′-Dicyclohexylmethane diisocyanate. By fine-tuning the bio-based diols, the hydrogen bond distribution and the crosslink density of the network were adjustable. The thermal mechanical properties and stress relaxation properties of the bio-based polyurethane were optimized. The bio-based polyurethane CANs shows tensile strength of 38.1 MPa, elongation at break of 243% and toughness of 55.7 MJ m −3, which is outstanding among most reported bio-based CANs. In addition, the polymer has excellent water resistance, shape memory and re-deformability. Due to the dissociation of imine bonds under mild acid conditions, the carbon fiber composite can readily degrade in mixed solvent for 3 h at 60 °C and the properties of recycled carbon fibers are highly preserved. Graphical abstract: Fabrication of extraordinary mechanical properties, reprocessably, and degradable polyurethanes through network structure design. Image 1 Highlights: Nonplanar rigid ring of isosorbide brings extraordinary mechanical properties to bio-based polyurethane CANs. Adjusting the ratio of diols can tune the degree of cross-linking and distribution of hydrogen bonds in the networks. Isosorbide can also improve fluidity of the network and lower activation energy. CF composites can be chemically degraded under mild conditions for non-destructive recycling of CF.